IMPORT SUBSTITUTION AND ENSURING FOOD SECURITY OF RUSSIA - I. G. Ushachev (Ovoŝi Rossii, 2019)
The article discusses the issues of import substitution in the market of agricultural products and resources for their production in Russian Federation, ensuring the country's food security. Research results show that since 2014, when the active import substitution policy began, there have been significant changes in the agri-food trade, characterized by a decline in imports and an increase in exports. However, in different product segments of the market the speed of these changes varies. Despite ensuring the country's food independence for most types of agricultural products, the dependence on the import of resources for its production remains significant. At the same time, the demand for agricultural products remains under pressure from declining household income, as well as a significant income differentiation. In this regard, suggestions were made for making adjustments to the doctrine of food security, primarily in terms of assessing the economic affordability of food. Also, an assessment was made of the changes made to the state program for the development of agriculture in conjunction with the strategic objectives of the development of the Russian Federation defined for the period up to 2024. The need to ensure consistency between the tasks assigned to the agro-industrial complex to achieve the country's food security, increasing the export potential of the domestic agri-food products and resources allocated for development, was noted.